PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN TETAP DI PT. CITRANUSA INTISAWIT - Rianto, Fajar Mukti; Yurisinthae, Erlinda; Hutajulu, Josua Parulian (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aims to analyze the effect of motivation and work environment on job satisfaction of permanent employees at the palm oil mill of PT. CitraNusa IntiSawit in Kedukul Village, Mukok District, Sanggau Regency. The population of the study is all permanent employees of the palm oil mill PT. CitraNusa IntiSawit. Sampling used in this study using the Slovin formula, the sampling that the author did was as many as 57 people. Data collection was done by questionnaire method, the data obtained were analyzed using multiple linear regression analysis to test the effect of motivation and work environment on permanent employee job satisfaction. Based on the results of statistical tests on multiple linear regression analysis, the variables of motivation and work environment have a positive effect jointly on job satisfaction of permanent employees. The results showed that partially the motivation variable did not significantly influence the job satisfaction of permanent employees, whereas for the work environment variable significantly affected the job satisfaction of permanent employees.